Pengaruh Relaksasi Benson Terhadap Penurunan Tingkat Kecemasan Pada Pasien Pre Operasi Di Ruang Dahlia RSUD Kota Tanjungpinang - Sri Hartini (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Anxiety is a mistake, doubt in something that will happen with an unclear cause or object related to feelings of uncertainty such as worry about facing surgery. To overcome anxiety, there are types of therapy that can be applied by nurses, namely pharmacological therapy and non-pharmacological therapy. One type of non-pharmacological therapy that can be used is the Benson relaxation technique. This study aims to determine the effect of Benson relaxation on reducing anxiety levels in pre-operative patients in the Dahlia Room, Tanjungpinang City Hospital. The design of this research is a pre-experiment with one group pretest posttest type. The number of samples in this study was 21 preoperative patients using the Accidental Sampling technique. The instrument used was the Amsterdam Preoperative Anxiety And Information Scale (APAIS) questionnaire. Then analyzed using the non-parametric Wilcoxon test. Univariate results before being given Benson relaxation showed that 33.3% had mild anxiety, 66.7% had moderate anxiety, and after Benson relaxation 85.7% had mild anxiety, 14.3% had moderate anxiety. Bivariate results show that the hypothesis is accepted with a p-value of 0.000. It was concluded that there was an effect of Benson relaxation on reducing anxiety levels in pre-operative patients in the Dahlia Room, Tanjungpinang City Hospital. From this research, it is hoped that the Benson relaxation technique can be used as an alternative therapy to reduce patient anxiety levels that does not have harmful side effects for patients.